2017
DOI: 10.1021/acs.iecr.7b01536
|View full text |Cite
|
Sign up to set email alerts
|

ZIF-8 Membrane Ethylene/Ethane Transport Characteristics in Single and Binary Gas Mixtures

Abstract: Zeolitic imidazolate framework-8 or ZIF-8 membranes have shown great promise in separating propylene/propane (C3) mixtures; however far fewer works have analyzed ethylene/ethane (C2) transport behavior in ZIF-8 membranes. This work studies C2 permeation behavior, transport properties, and selectivity as a function of temperature and pressure in single and binary gas mixtures. In single and binary separation tests conducted from 25 to 100 °C, the permeances of ethylene and ethane show a negative correlation wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
36
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 42 publications
9
36
0
Order By: Relevance
“…As a result, they have been used in the preparation of composite membranes and films for gas and liquid separation . Among them, ZIF‐8 (a representative Zn‐based ZIF material) has been widely studied as the intricate Zn−N coordination in ZIF‐8 enables a large pore (11.6 Å) for low resistance transport (high permeability) of molecules through the ZIF‐8 pore and a small nominal pore aperture (0.34 nm) excellent for molecular exclusion ( Figure ) …”
Section: Proton Conductivity In Metal‐organic Frameworkmentioning
confidence: 99%
“…As a result, they have been used in the preparation of composite membranes and films for gas and liquid separation . Among them, ZIF‐8 (a representative Zn‐based ZIF material) has been widely studied as the intricate Zn−N coordination in ZIF‐8 enables a large pore (11.6 Å) for low resistance transport (high permeability) of molecules through the ZIF‐8 pore and a small nominal pore aperture (0.34 nm) excellent for molecular exclusion ( Figure ) …”
Section: Proton Conductivity In Metal‐organic Frameworkmentioning
confidence: 99%
“…Although showing an excellent kinetic selectivity for propylene and propane, ZIF‐8 shows a much lower kinetic selectivity (≈5) for ethylene and ethane according to the analysis of gas uptake kinetics by in situ infrared microscopy (IRM) and pulsed field gradient nuclear magnetic resonance (PFG NMR) . This was ascribed to the relatively smaller sizes of the C2 gases and the sizable entropic selectivity of ZIF‐8 limited by the zeolitic pore shape …”
Section: Metal–organic Framework For Adsorptive Light Olefin/paraffimentioning
confidence: 99%
“…[155] This was ascribed to the relatively smaller sizes of the C2 gases and the sizable entropic selectivity of ZIF-8 limited by the zeolitic pore shape. [156] Recently, Peng et al reported two ultramicroporous MOFs, namely Zn(ox) 0.5 (trz) (ox = oxalate, trz = 1,2,4-triazole) and Zn(ox) 0.5 (atrz) (atrz: 3-amino-1,2,4-triazole), for kinetic propylene/propane separation. [157] These MOFs are constructed by pillaring of Zn-triazolate layers with the oxalate groups, and exhibit 1D zig-zag channels along the crystallographic a-axis with narrow necks of diameters of 2.6 and 2.9 Å for Zn(ox) 0.5 (trz) and Zn(ox) 0.5 (atrz), respectively.…”
Section: Kinetic Olefin/paraffin Separationsmentioning
confidence: 99%
“…The dissimilarity in separation efficiency observed between the single gas and the mixed gas measurements were attributed to the difference in experimental conditions. Later on, the transport properties of ethane/ethylene separation in the same (ZIF-8) membrane were studied by James et al at different temperatures ranging from 25 to 100 °C and different pressures [161]. Figure 61.…”
Section: Hydrocarbons Separationmentioning
confidence: 99%